Direct observation of frictional seizure by X-ray imaging - Margam Chandrasekaran. (2008)
Research has been concentrated on the evaluation of behaviour of frictional pairs in an attempt to improve their shelf life. Despite the efforts to obtain a better understanding of the behaviour of frictional systems, a convincing theory has yet to be established on the mechanism of scoring or scuffing. In-situ observation of frictional contacts was previously performed using either a scanning electron microscope or closed circuit digital camera and was restricted to the observation of leading and trailing edges of the contact. Recent work on in-situ observation of seizure facilitated use of idealized contact of sapphire disk. The present work was aimed at the in-situ observation of seizure by using an X-ray microscope (real time radiography), in practical contacts. This technique facilitates observation of interface during the testing which is not normally possible with the known techniques in case of non-idealized practical contacts.